Lessons from the success and failures of peritoneal Dialysis-Related Brucella Peritonitis in the last 16 years: Case report and Literature review - Bukhari, Muhammad; Mohammed, Azharuddin; Al-Guraibi, Abdullah; Shahata, Ahmed; Al-Ghamdi, Mansour (Journal of Clinical Nephrology, 2018)
Brucellosis is a zoonotic infection that is endemic in some Mediterranean countries, North Africa and the Middle East. Brucella is a rare cause of peritonitis in Peritoneal Dialysis (PD) population and in non-dialysis patients alike. We report here a challenging case of PD-related Brucella peritonitis in a 45-year-old Saudi male with late peritonitis that delivered some key learning throughout its course from presentation, diagnosis and treatment to catheter salvage attempts so as to circumvent PD failure. We provide an in-depth review of limited published literature on PD-related Brucella peritonitis (seven cases, and present case) and summarized the data on key clinical characteristics, management and PD technique outcome to benefit nephrologists when encountered with this rare presentation.